Peningkatan Kepuasan Pasien Melalui Kepercayaan, Fasilitas, Dan Kualitas Pelayanan - Dewi, I Gusti Ayu Candra; Benni Kusyana, Dewa Nyoman (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Problems related to the papacy should be addressed by every company immediately. Success in satisfying customers will get a better competitive advantage. The study was conducted in order to find out how the influence of trust, facilities, and service quality on outpatient satisfaction at Alin’s Medical Clinic in Petang Badung. During 2020 as many as 5,588 people used clinical services so that this number was used as the population and for the specified sample, there were 98 respondents. Analysis of research data will be carried out using the method of multiple linear regression analysis. From the results of the study, it was found that trust, facilities, and service quality were able to have a positive and significant impact on patient satisfaction. Suggestions put forward by researchers from the results of the study are to continue to encourage patient satisfaction by taking into account the factors of trust, facilities, and quality of service.